The information economy and American cities - Drennan, Matthew P., 1937- (Johns Hopkins University Press, 2002)
Annotation How can metropolitan regions remain prosperous and competitive in a rapidly changing economy? Challenging some long-standing assumptions, Matthew Drennan argues that those regions that have invested heavily in the information economy have done much better than those that continue to rely on manufacturing and industry as their base. Moreover, he contends, the benefits of that growth reach the urban working poor, earlier reports to the contrary notwithstanding. The Information Economy and American Cities provides a wealth of rigorously analyzed econometric data which will be of great value to economists, planners, and policymakers concerned with the future of America's metropolitan areas. Additional supporting data will be made available online. Not just another glib cheer for the information economy, this book provides the kind of hard evidence needed to advocate effectively for change.